The Naco Clovis Site: Old Excavations and New Dates. (3rd July 2022) - Huckell, Bruce B.; Haynes, C. Vance; Holliday, Vance T.; Hodgins, Gregory W. L.; Huckell, Lisa W.; Watkinson, Gina M.
ABSTRACT: Archival research demonstrates that a previously unpublished second season of excavations took place at the Naco Clovis site in 1953, more than doubling the extent of the excavated area and revealing additional bones pertaining to a second mammoth. In 2020 small pieces of charcoal were found in sediment adhering to the distal fragment of a mammoth ulna from the Naco site. The bone was part of a 2011 donation to the Arizona State Museum by David Navarrete, grandson and nephew of the original discoverers of the site. Three AMS radiocarbon dates were obtained from individual wood charcoal fragments, and two more on a sample of multiple charcoal flecks. The first three have a weighted mean of 10, 985 ± 56 14 C yr BP (13, 067–12, 767 cal yr BP), fitting within the range of Clovis ages obtained from other Clovis sites; the other two ages are younger.